Assessment of Heavy Metals and Microbial Load in Tomato Ketchup Used in Local Market of Southern Punjab - Husnain, Ghulam; Ahmad, Fraz; Khan, Fatima Afzal; Shahzad, Muhammad Ahsan; Mahmood, Saba; Muneer, Iqra; Shabbir, Hassan; Zeeshan, Muhammad; Saeed, Anam; Sajjad, Qamar (Indus Journal of Bioscience Research, 2025)
Tomatoes are globally renowned as one of the most widely cultivated agricultural commodities, indispensable staples in people's everyday diet. Tomato ketchup is susceptible to several types of microbiological contamination that could potentially pose a risk to the product purity. So, the main purpose of this study is to evaluate the presence of heavy metals and microbial containments in locally available ready to eat tomato ketchup in Multan. Results indicated that while levels of heavy metals such as lead and cadmium in some samples were near or exceeded permissible limits, unlikely can cause health hazards. Nonetheless, prolonged exposure could pose significant health hazards. The widespread use of wastewater in agriculture and increasing urbanization contribute to this contamination. All tested samples exhibited bacterial counts exceeding recommended reference levels, highlighting potential health concerns. The study underscores the importance of regular monitoring and provides a basis for effective risk communication and management strategies related to food safety. The study concludes that locally branded ready-to-eat tomato ketchup in Multan poses minimal risk regarding heavy metal contamination. However, non-branded ketchup samples showed higher chances of containing heavy metals and microbial contaminants, making them potentially harmful. While current levels of lead (Pb) and cadmium (Cd) may not cause immediate health effects, prolonged exposure could lead to serious health concerns. Urbanization, metal processing technologies, and wastewater use in farming contribute to increased contamination. All samples exceeded acceptable bacterial counts, highlighting the need for strict monitoring. Ensuring food safety requires regular surveillance of both heavy metal content and microbiological quality in processed foods.